2021
DOI: 10.36909/jer.14591
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of corrosion resistance and mechanical properties of API 5L X60 steel by heat treatments in different environments

Abstract: Steel pipelines are commonly used in the petroleum industry where high strength and durability values are required. In oil installations, the problems of corrosion, especially with crude oil, appear clearly and dramatically, in dealing with API 5L series. Improving the corrosion protection and mechanical properties are a genius goal for steel manufacturers, the heat treatment processes are familiar with this field. In this study, experimental investigations were executed to find the heat treatment influence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Thus, the differential equation for the temperature distribution in dimensionless form (corresponding to a constant cross section fin), in terms of the Biot number, is given by (Lieth et al, 2021):…”
Section: Methods and Validation A Introductory Elements On Heat Trans...mentioning
confidence: 99%
“…Thus, the differential equation for the temperature distribution in dimensionless form (corresponding to a constant cross section fin), in terms of the Biot number, is given by (Lieth et al, 2021):…”
Section: Methods and Validation A Introductory Elements On Heat Trans...mentioning
confidence: 99%
“…Firstly, 100 mL of NaCl and H2SO4 solutions with the same molar concentration (0.017 M) were prepared in a different compartment. After that, a rectangular shape of SS 316L was prepared with a dimension of 20 mm x 10 mm x 2 mm and hanged with a inert rope [38,39]. Fig.…”
Section: Corrosive Medium Immersion Testmentioning
confidence: 99%
“…Lieth et al investigated effects of heat treatment on different water condition i.e., sea water, fresh water, and crude oil by immersion method. They found that the severe corrosion occurred in the sea water at high temperature [21]. Another study by Ji et al found that the higher the concentration of the mixed solution and the higher the test temperature, the greater the corrosion rate of 316L stainless steel wire and the lower the breaking strength of 316L stainless steel wire [22].…”
Section: Introductionmentioning
confidence: 99%
“…These activities lead to the metal degrading. Corrosion leads to a decrease in the steel's mechanical properties, causing a reduction in thickness, strength, and tenacity, as well as material degradation [2], thereby resulting in an approximately 80-90% failure in this sector. However, methods for controlling or improving such an occurrence has become a research focus.…”
Section: Introductionmentioning
confidence: 99%